Comparative Assessment of Gold Nanoparticle–Antibody Conjugates with Two Differently Shaped Particles for Multimodal Colorimetric Lateral Flow Assay - Vinayak Sharma; Bilal Javed; Furong Tian (Proceedings)
Novel detection strategies that exploit the unique properties of gold nanoparticles (AuNPs) hold great potential for the advancement of point-of-care (POC) diagnostics, such as lateral flow and dipstick immunoassay [...]